2014
DOI: 10.2190/ec.51.3.c
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Geometry Software Improves Mathematical Achievement: Systematic Review and Meta-Analysis

Abstract: Dynamic geometry software (DGS) aims to enhance mathematics education. This systematic review and meta-analysis evaluated the quasi-experimental studies on the effectiveness of DGS-based instruction in improving students' mathematical achievement. Research articles published between 1990 and 2013 were identified from major databases according to a prespecified search strategy and selection criteria. A meta-analysis was conducted based on the random-effects model to evaluate the effectiveness of DGS-based instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 24 publications
6
38
3
Order By: Relevance
“…Besides manipulatives, the success of students completing assignments is also assisted by Geogebra. Dynamic geometry software aims to enhance mathematics education (Chan & Leung, 2014). Geogebra is a software system that integrates the possibilities of both dynamic geometry and computer algebra in one tool for mathematics education.…”
Section: Figure 16 Student Answer Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…Besides manipulatives, the success of students completing assignments is also assisted by Geogebra. Dynamic geometry software aims to enhance mathematics education (Chan & Leung, 2014). Geogebra is a software system that integrates the possibilities of both dynamic geometry and computer algebra in one tool for mathematics education.…”
Section: Figure 16 Student Answer Numbermentioning
confidence: 99%
“…Research shows that the learning of circle by the traditional method, without using manipulatives or geometry software, significantly influence student's negative attitude and high student anxiety level (Budiman, 2014). The statistically significant and high overall effect of dynamic geometry software-based instruction on students' mathematical test scores demonstrated that Dynamic Geometry Software intervention should be an effective approach to transforming traditional teaching practices (Chan & Leung, 2014). The use of manipulatives will assist students in constructing an understanding of mathematical concepts.…”
Section: Introductionmentioning
confidence: 99%
“…In a review, Chan and Leung (2014) examined nine quasi-experimental studies, which included a total of 587 participants, comparing groups of students using software such as Cabri Geometry and Geometer's Sketchpad to students working with pen and paper. They found a distinct effect size in favor of the use of dynamic software.…”
Section: Dynamic Software Problem Solving and Learning Outcomesmentioning
confidence: 99%
“…One suggestion for enhancing learning involves the use of technology, in this case dynamic software. Several studies have compared the learning outcomes of students using dynamic software with those of students using pen and paper, and they report that students using dynamic software outperform the latter, as the technology offers students an interactive environment in which to explore and engage in reasoning and creative problem solving (Chan and Leung 2014;Diković 2009). Another question concerns task design, and whether students learn better solving guided tasks, where students are given instructions on how to solve (parts of) the task, or if it is more beneficial to provide students with problems, that is, unguided non-routine tasks that they solve by constructing at least part of the methods themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analytic thinking is defined as the prospective formulation of study expectations and design by explicitly invoking prior effect sizes and the retrospective interpretation of new results by direct comparison with prior effects in the related literature (Thompson, 2002, p. 28). Numerous meta-analytic studies have investigated technology's effect on mathematics achievement and the factors that mediate these effects over the last three decades (Chan & Leung, 2014;Hembree & Dessart, 1986;Li & Ma, 2010). This growing body of research currently informs classroom practices in the U.S. and beyond.…”
Section: Introductionmentioning
confidence: 99%